Cell signaling in Ehrlichia infection and cancer: Parallels in pathogenesis - Solomon, Regina N.; Pittner, Nicholas A.; McCoy, Jaclyn R.; Warwick, Paityn A.; McBride, Jere W. (Frontiers in Cellular and Infection Microbiology, 2025)
Ehrlichia chaffeensis (E. chaffeensis) has recently emerged as an intracellular bacterial pathogen with sophisticated survival mechanisms that include repurposing evolutionarily conserved eukaryotic cell signaling pathways for immune evasion. E. chaffeensis exploits four major developmental signaling pathways (Wnt, Notch, Hedgehog, and Hippo) using short linear motif (SLiM) ligand mimicry to initiate signaling cascades. Dysregulation of these major signaling pathways leading to unchecked cell survival is implicated in various diseases, most notably cancer. E. chaffeensis exploits Wnt, Notch, Hedgehog and Hippo signaling pathways to inhibit apoptosis and co-opt other cellular functions to promote infection. This review will explore the signaling pathways exploited during Ehrlichia infection and the new discoveries that have illuminated this interesting example of the cell signaling convergence in cellular infection and cancer biology.